Finding Space For African Population Health - Agyei-Mensah, S. (University of Ghana, 2015)
The concept of space in its multiple forms, is central to the theoretical and methodological foundations of health and population geography. In this lecture, I examine the way space has shaped and continues to shape our understanding of population and health issues in Africa, and explore the unique contribution to be derived from closer linkages between population health and spatial analysis. Methods and models are needed that link individual and aggregate analyses, bridge geographic scales, and couple space and time. These approaches would augment theory, advise policy, and address the existing dearth of knowledge; but call for new methods of data collection and also have implications for population and health training. Illustrations will be drawn from my individual and collaborative work on population and health issues within the Ghanaian and African contexts.
Keywords: African Population; Health